Reflection or mirage? The problem of the relationship between online and offline identities in the context of interpersonal communication - Gharagulyan , Arman (Bulletin of Yerevan University E: Philosophy, Psychology, 2023)
The relationship between online and offline identities in today's digital era is a pivotal in the realm of interpersonal communication research. As modern technology rapidly evolves, it brings forth unprecedented avenues for social interactions, amplifying inherent human need to connect and socialize. Social media platforms, along with modern remote communication tools, are reshaping our conventional notions of work, education, and leisure. This transformation introduces a contemporary "virtual" framework for interpersonal relations. Nowadays individuals increasingly immerse themselves in these digital realms, crafting unique online personas to represent their virtual selves. Consequently, people now navigate two parallel universes: the tangible and the digital. This article delves into the nuances of online identity, its interplay with our real-world persona. It examines how our digital footprints mesh with, or at times diverge from, our real-world personas and the emerging challenges and opportunities of this online-offline dynamic within interpersonal relationships.  Moreover, the piece offers a comprehensive review of potential issues stemming from prioritizing the digital over the physical, while also highlighting the possible advantages that prudent digital technology usage can bring.Key words: Information Society, Social Networks, Digital World, Online Identity, Interpersonal Communication, Virtual Man
Keywords: Information Society; Social Networks; Digital World; Online Identity; Interpersonal Communication; Virtual Man